Process Parameters Dependence Of Acrylonitrile Butadiene Styrene (ABS) Flow Patterns Inside A Capillary Rheometer Barrel (Jurnal Teknologi (Sciences & Engineering), 2012)
Tujuan kajian ini adalah untuk membangunkan satu alternatif untuk mententukur satu isipadu tiga dimensi. Kerangka tentukuran baru ini menggunakan empat tiang yang mengandungi 20 titik kawalan. Satu eksperimen telah dilakukan untuk membandingkan keputusan yang didapati daripada dua kaedah tentukuran iaitu kerangka tentukuran Peak dan kerangka tentukuran ISN–UM (kerangka baru). Keputusan eksperimen menunjukkan bahawa kerangka tentukuran ISN–UM adalah sepadan dengan keputusan yang didapati daripada kerangka tentukuran Peak, walaupun kedudukan, jumlah titik kawalan dan sifat fizikal kedua-dua kerangka berbeza. Kata kunci: Tentukuran; sistem tiang; biomekanik sukan The purpose of this study is to develop an alternative method for calibrating a three-dimensional volume. The new calibration frame uses a set of four poles, consisting of 20 control points. An experiment was conducted to compare the result obtained using two methods of calibration, the Peak calibration frame (the control) and the ISN–UM survey poles system (the new reference frame). It was found that the results obtained from the ISN–UM calibration frame are comparable to those obtained using the Peak calibration frame, despite the differences in the locations and the numbers of control points, as well as the physical characteristics of both structures. Key words: Calibration; survey poles system; sports biomechanics